2013
DOI: 10.1038/nrn3405
|View full text |Cite
|
Sign up to set email alerts
|

The impact of microsaccades on vision: towards a unified theory of saccadic function

Abstract: When we attempt to fix our gaze, our eyes nevertheless produce so-called 'fixational eye movements', which include microsaccades, drift and tremor. Fixational eye movements thwart neural adaptation to unchanging stimuli and thus prevent and reverse perceptual fading during fixation. Over the past 10 years, microsaccade research has become one of the most active fields in visual, oculomotor and even cognitive neuroscience. The similarities and differences between microsaccades and saccades have been a most intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
370
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 424 publications
(410 citation statements)
references
References 130 publications
21
370
1
2
Order By: Relevance
“…Saccadic eye movements are known to play multiple roles in vision-that is, they foveate high-interest targets, correct gaze errors, and search and integrate general information about the environment to stitch together the perception of a scene (7,35). Likewise, many microsaccade functions have been proposed (31), including the prevention of visual fading and the restoration of faded visual targets (36)(37)(38), the control of fixation position (3,39), and improved visual performance in high-acuity tasks (24,40). Our results point to a similarity in function for microsaccades and saccades, and suggest that all of the saccadic roles may be common to microsaccades, including the scanning and exploration of visual objects and scenes traditionally ascribed to (large) saccades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccadic eye movements are known to play multiple roles in vision-that is, they foveate high-interest targets, correct gaze errors, and search and integrate general information about the environment to stitch together the perception of a scene (7,35). Likewise, many microsaccade functions have been proposed (31), including the prevention of visual fading and the restoration of faded visual targets (36)(37)(38), the control of fixation position (3,39), and improved visual performance in high-acuity tasks (24,40). Our results point to a similarity in function for microsaccades and saccades, and suggest that all of the saccadic roles may be common to microsaccades, including the scanning and exploration of visual objects and scenes traditionally ascribed to (large) saccades.…”
Section: Discussionmentioning
confidence: 99%
“…Van Gisbergen and coworkers showed that the activity of excitatory burst neurons in the pontine reticular formation encodes microsaccades and saccades (30). No studies to date have conducted recordings from inhibitory burst neurons in connection with microsaccades, however (31). Omnipause neurons in the raphe stop firing during both saccades and microsaccades (32,33), and population activity in the superior colliculus map generates microsaccades and saccades in equivalent fashion (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…Microsaccades were distinguished from macrosaccades using an amplitude threshold of 1° (Martinez-Conde et al, 2013) and the median microsaccade amplitude was 0.65°(M1: 0.71°, M2: 0.65°, M3: 0.62°). This is larger than in most studies, although there is also considerable variability between the average microsaccade amplitudes described in past reports, which include 0.8° (Bair and O'Keefe, 1998) (Ko et al, 2010;Poletti and Rucci, 2010), and 0.23° ( Hafed et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Selection does not only control the access of task-relevant objects to working memory, but also provides spatial coordinates for upcoming eye movements. Research on saccades and microsaccades [65][66][67] has provided important insights into the control of selective attention during search in real-world visual scenes. For example, semantic and spatial expectations linked to particular scene contexts strongly constrain which parts of a scene will be visually examined [65,68], which demonstrates that high-level world knowledge plays an important role for attentional guidance and selection.…”
Section: Concluding Commentsmentioning
confidence: 99%